1972
DOI: 10.1063/1.1661507
|View full text |Cite
|
Sign up to set email alerts
|

Role of Copper in the Degradation of GaAs Electroluminescent Diodes

Abstract: The degradation associated with prolonged operation of GaAs diodes under large forward bias has been investigated. It is observed that the degradation rate increases with temperature and that the fractional percent degradation per unit time interval increases as exp (−E0/KT) for most devices. The value of E0 is about 0.45 ± 0.1 eV. It is shown that contamination of devices with copper increases the degradation rate. The 1.28-eV emission band in the degraded Cu-contaminated devices is enhanced relative to the b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

1973
1973
2011
2011

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(4 citation statements)
references
References 14 publications
0
4
0
Order By: Relevance
“…Implicitly contained in this reasoning is the assumption that Cu is not present on the cell prior to test. The detrimental effect of Cu on the performance of III‐V devices is well known in semiconductor manufacturing . Therefore, significant effort is undertaken there to avoid Cu contamination.…”
Section: Discussionmentioning
confidence: 99%
“…Implicitly contained in this reasoning is the assumption that Cu is not present on the cell prior to test. The detrimental effect of Cu on the performance of III‐V devices is well known in semiconductor manufacturing . Therefore, significant effort is undertaken there to avoid Cu contamination.…”
Section: Discussionmentioning
confidence: 99%
“…In LPE GaAs grown from Cu-doped melts, only the 0.14 and 0.44 eV levels are observed (41). Degradation of GaAs light emitting diodes has been associated with Cu contamination of the p-GaAs side of the junction (42). In GaP acceptor levels at Ev + 0.17, 0.64, and 0.82 eV have been reported (43)(44)(45) but Cu levels in GaAs0.6Po.4 appear not to have been studied.…”
Section: Results Of the Metal Diffusion Studiesmentioning
confidence: 99%
“…Although these results do not prove that copper was the cause of degradation, they show that reduction of either contamination or the number of point defects increased the LED life. Bahraman and Oldham (1972) similarly found that copper contamination of gallium arsenide LEDS significantly increased the degradation rates of their devices.…”
Section: Light-emitting Diodes (Low-current-density Devices)mentioning
confidence: 90%